2012
DOI: 10.1016/j.icarus.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Zonal winds at high latitudes on Venus: An improved application of cyclostrophic balance to Venus Express observations

Abstract: Recent retrievals of zonal thermal winds obtained in a cyclostrophic regime on Venus are generally consistent with cloud tracking measurements at midlatitudes, but become unphysical in polar regions where the values obtained above the clouds are often less than or close to zero. Using a global atmospheric model, we show that the main source of errors that appear in the polar regions when retrieving the zonal thermal winds, is most likely due to uncertainties on the zonal wind intensity in the choice of the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The values modelled have a latitudinal gradient of the zonal momentum very similar to solid body rotation. These results suggest the presence of atmospheric wave activity such as barotropic eddies, which tend to mix the atmosphere towards a state of approximately uniform absolute vorticity (Schubert et al 1999;Mendonça et al 2012), with consequent implications for the distribution of axial angular momentum and other variables.…”
Section: Comparing With Observational Wind Datamentioning
confidence: 90%
“…The values modelled have a latitudinal gradient of the zonal momentum very similar to solid body rotation. These results suggest the presence of atmospheric wave activity such as barotropic eddies, which tend to mix the atmosphere towards a state of approximately uniform absolute vorticity (Schubert et al 1999;Mendonça et al 2012), with consequent implications for the distribution of axial angular momentum and other variables.…”
Section: Comparing With Observational Wind Datamentioning
confidence: 90%
“…Mendonça & Read 2016). In Venus, numerical models and observations indicate the presence of a strong equatorial jet in the cloud region (e.g., Kerzhanovich & Limaye 1985;Sánchez-Lavega et al 2008;Moissl et al 2009;Mendonça et al 2012), where most of the incoming radiation from the sun is absorbed. In this case the transport of the upward propagating waves excited in the cloud region is the main mechanism accelerating the low latitude jet.…”
Section: Theoretical Motivationmentioning
confidence: 99%
“…For data gaps, we set it to zero, and for nonempty data points, we To evaluate the effect of the vertical shear of the background zonal wind on the propagation of planetary waves (Imamura, 2006;Kouyama et al, 2015), we used the thermal wind equation to calculate the background zonal wind and thus its vertical shear. The thermal wind equation we can infer from an isobaric coordinate system (Mendonça et al, 2012) is shown as follows:…”
Section: Data and Analysis Methodsmentioning
confidence: 99%
“…To evaluate the effect of the vertical shear of the background zonal wind on the propagation of planetary waves (Imamura, 2006; Kouyama et al., 2015), we used the thermal wind equation to calculate the background zonal wind and thus its vertical shear. The thermal wind equation we can infer from an isobaric coordinate system (Mendonça et al., 2012) is shown as follows: 2uuz=gT0.25emtan0.25emϕTϕp, $2u\frac{\partial u}{\partial z}=\frac{g}{T\,\mathrm{tan}\,\phi }{\left(\frac{\partial T}{\partial \phi }\right)}_{p},$ …”
Section: Data and Analysis Methodsmentioning
confidence: 99%